Social and Economic Life in The Public Class of Iraqi Society in The Abbasid Period - Hassan, Mohammed S. (Humanities Journal of University of Zakho, 2017)
The study of the Islamic community of important historical topics, which reveal the manifestations of Islamic civilization, which did not devote sufficient efforts to reveal and highlight the existence and highlighted some pages of our history of the bright social structure of the various layers of the Islamic community, so the research derived the article from multiple parables and address the history of the community Especially the Iraqi public class, Which includes in its composition the industrialists, craftsmen, farmers and various types of society, such as the profiteers of tanning, Hamalis, Smakin, vendors of flour, hiccups, and many others, such as grooms and rattles. This class was dominated by the characteristics of the poor class: poverty, deprivation, poverty and urgent need. Of whom are from the people of Dharma, Thanks to the patronage and encouragement of the Abbasid state to the craftsmen and craftsmen, some Iraqi industries became famous internationally, especially the textile industries, as well as farmers from villages and rural areas in Iraq who were engaged in agriculture and farming the land. This category of the public class was the majority of the population of Iraq in the Abbasid era, while the caliber were belonging to the layers of popular workers, a group of the public rushed to improve their economic conditions miserable by taking various methods of robbery and theft and theft using the weapon to achieve their goals, As well as the fugitives who are a group of the public also works in the looting and the use of ways and means of violent to achieve their goals have been active during the events of the year (197 AH / 812 AD) after the siege of Baghdad, and thus revealed Baghdad and other cities in Iraq thousands of author This is what leads to the fact that these actions are only a result of the public's suffering from the decline of their political and economic conditions. However, this class has had a great role in Iraqi society in terms of political, social and economic.